2011
DOI: 10.4028/www.scientific.net/amr.368-373.771
|View full text |Cite
|
Sign up to set email alerts
|

Study on Safety of the Fastener Tubular Steel Scaffolding

Abstract: Based on analysis of five different conditions’ full scale model tests of the fastener tubular steel scaffolding, the paper introduces that notional lateral loads can imitate the effect which generalized imperfections of the falsework(initial imperfections, node semi-rigid and so on) give the bracket’s stability capacity. According to the finite element software ANSYS, the falseworks’ stability capacities of different conditions have been imitated and analysed, Analysis results compare with test results. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Recent research in China has been undertaken on theoretical and experimental models of tube-and-fitting scaffolds. Hu et al [79][80][81] undertook experiments on scaffold assemblies and showed that when the imperfections in the scaffold were correctly modeled that correspondence was made with analytical models. Li et al [82] developed a semiempirical design tool for the analysis of scaffolds and compared the results with a finite element program with good correlation.…”
Section: Tube-and-fitting Modelsmentioning
confidence: 99%
“…Recent research in China has been undertaken on theoretical and experimental models of tube-and-fitting scaffolds. Hu et al [79][80][81] undertook experiments on scaffold assemblies and showed that when the imperfections in the scaffold were correctly modeled that correspondence was made with analytical models. Li et al [82] developed a semiempirical design tool for the analysis of scaffolds and compared the results with a finite element program with good correlation.…”
Section: Tube-and-fitting Modelsmentioning
confidence: 99%